Les jeunes enfants à Bruxelles : d’une logique institutionnelle à une vision systémique - Perrine Humblet; Gaëlle Amerijckx; Stéphane Aujean; Murielle Deguerry; Michel Vandenbroeck; Benjamin Wayens (Brussels Studies, 2015)
In the Belgian federal system, matters related to persons are under the remit of the Community and not of the Region. But although matters such as education and culture are managed in a French- or Dutch-language framework, they are major challenges for Brussels. On several occasions, the Brussels Studies Institute synopses have dealt with the challenges of mainly Community matters in a Brussels perspective, in particular by gathering information and statistics for a consolidated inventory at regional level. After compulsory education, higher education and, to a certain extent, vocational training, the fifth synopsis and 91st issue of Brussels Studies continues along these lines by exploring the situation of young children, from birth to age 6.